2009
DOI: 10.1111/j.1365-2109.2009.02430.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of graded levels of dietarymyo-inositol on non-specific immune and specific immune parameters in juvenile Jian carp (Cyprinus carpiovar. Jian)

Abstract: The aim of this study was to evaluate the e¡ects of myo-inositol (MI) on non-speci¢c immune and speci-¢c immune defence in ¢sh. A total of 1050 Jian carp (Cyprinus carpio var. Jian) (22.28 AE 0.07 g) were randomly distributed into seven groups, of three replicates each, of feeding diets containing graded levels of MI (163.5, 232.7, 384.2, 535.8, 687.3, 838.8 and 990.3 mg MI kg À 1 diet). After a 60-day growth trial, an infectious trial was conducted by injection of Aeromonas hydrophila for 17 days. Results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 43 publications
3
16
0
Order By: Relevance
“…Immunity in fish is largely dependent on the growth of the immune organs [9]. Our previous study demonstrated that MI could enhance the growth of the head kidney and spleen in juvenile Jian carp [14]. These findings indicated that MI might influence immunity in the head kidney and spleen of fish, which required further investigation.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Immunity in fish is largely dependent on the growth of the immune organs [9]. Our previous study demonstrated that MI could enhance the growth of the head kidney and spleen in juvenile Jian carp [14]. These findings indicated that MI might influence immunity in the head kidney and spleen of fish, which required further investigation.…”
Section: Introductionmentioning
confidence: 93%
“…This study used the same animal trial described in our previous study [14]. The experimental diets and the preparation and storage of diets were the same as described in our previous study [14].…”
Section: Experimental Diets and Growth Trialmentioning
confidence: 99%
See 2 more Smart Citations
“…The requirement of dietary valine has been determined in juvenile grass carp [24] but may vary with the growth stage of the fish [25,26]. In addition, the requirements of nutrients may vary with the sensitive indicators [27,28]. Therefore, it is valuable to determine the valine requirements of grass carp based on the immune and growth indicators.…”
Section: Introductionmentioning
confidence: 99%